The Problem of Online Learning in Covid-19 toward Learning Process - Nindya Ananda Latifa; Lufri Lufri; Zulyusri Zulyusri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
Covid-19 has an impact on all aspects, including aspects of education. During the pandemic, the learning process is online. It minimizes direct interaction between individuals to break the chain of the spread of the corona-virus. The aim of this study was to find the problems during the online learning process. That it can be used as an evaluation material for a better learning process. The study was conducted with library research. Sources of research data obtained from articles, publication journals, books, and statically data. The analysis technique used content analysis of literature and articles with are the source of research data. The problem during the online learning process include a decrease in the enthusiasm for learning students, a lack of understanding of the material by students, and the effectiveness of online learning. Problems during the online learning process are expected to be an evaluation to be able to improve the learning process even better.